AN ANALYSIS OF THE USE OF HEDGES BY YOUNG CHILDREN - Uli Alfan Hasani; Dyah Indah Nugraheni; Muhammad Fikar Fauzi; Rolisda Yosintha (Yavana Bhasha : Journal of English Language Education, 2022)
Children tend to have simple pronunciation and language compared to adults. However, children will also experience language development according to their age such as Noah Ritter, who was five years old when interviewed by television stations until invited to the Ellen Show two years letter when Noah was seven years old. Noah Ritter is also nicknamed "The Apparently Kid" because he often says "apparently" in his sentences. In this case, there is a child who can speak using hedges whereas the hedges themselves are usually used by adults. This study aimed to describe the use of hedges in young children and explain some of the factors and causes why young children can use hedges like adults. The method used in this research was a descriptive qualitative method. For the results and discussion, the researchers found that a child can use hedges from many factors such as the environment from both family and friends and how often Noah Ritter always hears and imitates the language used by his parents. As a result, in language development, he can apply hedges. It can be concluded that the hedges used by children are the result of children imitating their environment because children often listen to adults talk and indirectly understand the context of their use even though they do not fully understand.